System process management with implement of diagnostics and service functions - Pupena, Alexander; Mirkevich, Roman; Klymenko, Oleh (My University, 2017)
We consider approached to develop a framework for application software programmable logic controllers as components of the base system process control (BPCS) with regard to their integration with other systems (SCADA, SIS, BPCS, MES/MOM) and increased requirements to the diagnostic process and service process and equipment.
Keywords: SCADA; SIS; BPCS; MES/MOM; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка